Composição corporal e exigências líquidas de minerais de cabras Moxotó em gestação, no semiárido nordestino - Maior Júnior, Rinaldo José de Souto (2012)
The objective was to evaluate the influence of gestational stage, number of fetuses and food restriction on the intake, mineral balance, mineral composition of the maternal body, the pregnant uterus and mammary gland, as well as to estimate the retention and the requirement net and dietary minerals Ca, P, Mg, Na and K Moxotó goats in pregnancy. This study was conducted in the Experimental Station of São Joao do Cariri Eight females goats not pregnant were slaughtered for represent initial body composition. A group of females goats able to breeding was submitted to estrus synchronization, through hormonal protocols and those presenting estrus were mated in the breeding. Thirty days after the first mated, it was made a pregnant diagnostic and the checked the number of fetuses. After confirmed the gestation and determined the number of fetuses, the female goats were grouped according to gestation day (50, 100 and 140 days), type of gestation (single or double) and the level of food restriction (0%, 20% and 40% of restriction). It was used a completely randomized design in factorial arrangement 3 x 2 x 3. The female’s goats remained in individuals barns and were slaughtered in the different days of gestation. For the assessment of the intake and minerals balance, were used only the goats that were slaughtered in the 140 days of gestation. The metabolism digestibility was made in three different periods: from 35 to 50 days, from 85 to 100 and from 125 to 140 days. Were collected laboratory sampling separated of body in the goats, uterus, fetus and mammary gland for the laboratories analyses to determination of the minerals. The prediction model used for the minerals was MC = β0 × EBW β1, as MC = mineral content and EBW is empty body weight. It was observed that gestational age affected the intake and minerals balance of Moxoto goats in confinement and in lowest percentage the number of fetuses and level of restriction. The gestational age influenced the minerals concentration in the body maternal, pregnancy uterus, fetus and mammary gland, whereas that the number of fetuses influenced only the mineral composition of the pregnancy uterus and the fetuses of females goats. The level of food restriction not caused bigger changed in the variables and there are significant diferences in the net requirements of minerals for the moxoto female goats to 50,100 and 140 days of gestation, independent of the number of fetuses.